Pertanggungjawaban Hukum Anak dalam Tindak Pidana Membawa Senjata Tajam - Rahmawati, Nila; Idran, Mohammad; Abdurrachman (Legalita, 2024)
This article examines Indonesia's Juvenile Justice System (SPPA), highlighting persistent challenges. Two key research questions are explored: (1) How does Indonesia hold children accountable for sharp weapon crimes? (2) What factors hinder effective justice for child offenders? The study employs normative and qualitative approaches, revealing inconsistencies in restorative justice, environmental factors and character education gaps. Diversion programs show potential but face limitations due to law enforcement's lack of understanding and resources. To foster a fair justice system, the study recommends enhanced character education, law enforcement training and rigorous oversight, ultimately supporting Indonesian children's positive development. Effective implementation requires addressing social environment, peer pressure and character education deficiencies through holistic approaches. Further research is necessary to optimize SPPA's effectiveness.